The local impacts of agricultural subsidies: Evidence from the Canadian Prairies - Ray D. Bollman; Shon Ferguson (Research Institute of Industrial Economics (IFN), 2016)
We estimate the impact of the removal of a railway transportation subsidy on the local economies of Alberta, Saskatchewan and Manitoba, exploiting the large regional variation in these one-time freight rate increases. We find that higher freight rates - and hence lower farm gate prices - resulted in significantly lower farm revenues, farm asset values and farm numbers. Local employment in non-agricultural sectors systematically declined in areas that were hardest hit by the subsidy removal. The results suggest that the subsidy removal had detrimental spillover effects on local non-agricultural economy that are much larger than standard input-output models would predict.
Keywords: F14; O13; Q16; Q17; Q18; 330; Agricultural Trade Liberalization; Export Subsidy; Market Access; Spillovers